Bio-efficacy of deltamethrin based durable wall lining against wild populations of Anopheles gambiae s.l. in Northern Tanzania. (December 2017) - Kweka, Eliningaya; Lee, Ming-Chieh; Mwang'onde, Beda; Tenu, Filemoni; Munga, Stephen; Kimaro, Epiphania; Himeidan, Yousif
Abstract Background Indoor residual spraying (IRS) is one of the preferred tools used for control of malaria in many settings in the world. However, this control tool still faces challenges that include lack of long lasting active ingredient, limited number of well-trained personal, and need of repeated treatment which increases operational costs and reduces acceptability by residents. As a result there is need to develop and validate other methods which can complement the existing controls. The current study compared the bio-efficacy of durable wall lining (DL) (treated with deltamethrin 265 mg/m2 ) and IRS (with deltamethrin 5% WP at 20 mg/m2 ) on indoor mosquitoes densities and biting behaviour of mosquitoes in comparison with control houses without either DL or IRS. Methods A study with two treatment arms and a control was conducted in Magugu ward, Northern Tanzania. Overall, a total of 60 houses were selected for the study with 20 houses per treatment arm and control. From each arm and control five houses were selected for mosquitoes trapping. Mosquitoes were sampled from 18:00 to 07:00 hourly every month for a period of 6 months. Mosquitoes were sampled using CDC miniature light traps. Results A total of 14, 400 female wild mosquitoes were used for contact bioassays in the control arm. 20 houses were sprayed, additionally walls of 20 houses were installed with wall liners, and walls of 20 unsprayed houses were used as control. Also, a total of 946 mosquitoes were sampled with traps in 60 houses during the hourly sampling for 6 months. A total of 3000 unfed females ofAn. gambiae s.l. wild population raised from larvae were collected from natural habitats in the same village for bioassays. The decline in indoor mosquitoes densities observed in this study did not lead to a shift in the biting cycles (P = 0.712). The number of mosquitoes caught indoors in houses with DL and IRS was significantly lower (P < 0.001) compared to control houses. When the comparisons were done between DL and IRS houses, the densities were significantly lower in DL houses compared to IRS houses (P = 0.021). In the DL installed houses, indoor mosquito density declined notably and sustained throughout the 6 months of the study. However, in those houses sprayed with deltamethrin 5% WP (PALI™5 WP), the density noted to start to increase within four months after spraying(do you mean to say that the densities declined up to 4 months post spraying and thereafter increased. Conclusions Considering the efficacy duration of DL against IRS with deltamethrin 5% WP on mosquito densities decline indoors. The results of this study suggest that DL is more effective in malaria control as its efficacy lasted more than that of IRS.